Language contact and morphological competition: Plurals in central Sicily. (July 2021) - Cruschina, Silvio
Abstract : This paper explores the effects of language contact in the nominal morphology of central Sicilian dialects. In particular, this study is concerned with the contact-induced changes related to the distribution of three plural formatives that give rise to competition between different inflectional classes with respect to a number of lexemes. It is shown that sociolinguistic factors such as speaker age account for the distribution of the competing plural forms and the high degree of variation. As a consequence, a slow and gradual change is leading to the disappearance of the plural form that has no equivalent in the contact language, that is, in Italian.